Blended Learning Practice in Russia: the History of one Experiment - Andreyeva N.V (Moscow State University of Psychology and Education, 2018)
The paper describes various approaches to the definition and implementation of blended learning in Russia and gives a brief overview of its development in Russia, focusing especially on one experimental case of introducing blended learning in one of the Moscow schools. The experiment lasted for two years and included students of four 5th-6th classes. The results suggest that blended learning in Math lessons has a positive effect on the quality of intersubject and metasubject educational outcomes. It is argued that such an improvement is not the effect of a particular, unique model of blended learning, but of a model which integrates a number of factors influencing the educational outcome. Supposedly, this result is achieved due to interim assessments and the teacher's individual work with children who have difficulties with mastering new material and/or have not fully understood previous topics.